Searching for the “median Judge”: study of coalition formation in the third chamber of the Chilean Supreme Court - Pardow Lorenzo, Diego; Carbonell Bellolio, Flavia (Revista de Ciencia Política, 2018)
This work adapts the traditional methodology of dissent analysis for approaching to the judicial behavior of the Chilean Supreme Court between 2009 and 2013, particularly its Third Section. Although the high proportion of unanimous decisions (90% of the total) and the huge workload (500 cases per judge) generate limitations, our analysis finds robust coalitions in an environment of variability with over 10 different compositions per year in the same court. Within this period, the behavior of the court seems dominated by the coalition of justices Pierry, Carreño and Araneda, who form the majority when the court splits. Regarding the dissenting justices, the first part of the period features an opposition with Brito, and the second with Muñoz. Whereas both justices appear in a solitary position as the minority, Pierry seems to behave as a “median justice.”